2016
DOI: 10.1007/s11136-016-1461-9
|View full text |Cite
|
Sign up to set email alerts
|

Development of the forensic inpatient quality of life questionnaire: short version (FQL-SV)

Abstract: This study has shown that the FQL-SV is a psychometrically valid abbreviation of the FQL and can therefore be used to monitor or assess QoL in forensic psychiatric care. However, when certain domains should be targeted in treatment, the FQL (full version) can assist both the patient and the clinician to get a more complete view of the individualized targets they should be aiming at in order to improve QoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…To that purpose, the Veneto REMS also included the WHOQoL-Bref in the battery of ROM instruments. The internal consistency of the Italian FQL-SV was good; the Cronbach's alpha was 0.86, which was higher than in the original version (28). Construct validity with the WHOQoL-Bref was largely in accordance with the results presented by Schel and colleagues (2016).…”
Section: Main Findingssupporting
confidence: 83%
See 1 more Smart Citation
“…To that purpose, the Veneto REMS also included the WHOQoL-Bref in the battery of ROM instruments. The internal consistency of the Italian FQL-SV was good; the Cronbach's alpha was 0.86, which was higher than in the original version (28). Construct validity with the WHOQoL-Bref was largely in accordance with the results presented by Schel and colleagues (2016).…”
Section: Main Findingssupporting
confidence: 83%
“…Improvement of objective indicators does not necessarily enhance the subjective evaluation and differences in subjective QoL can not necessarily be explained by objective indicators (25,26). Studies among forensic psychiatric patients have shown that a better QoL was related to (leisure) activities, living environment and health (27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%
“…Patient quality of life was measured with the short version of the Forensic Quality of Life Profile (FQL-SV; 45, 46). This scale was developed in The Netherlands and translated into English by its authors.…”
Section: Instrumentsmentioning
confidence: 99%
“…It has demonstrated good psychometric properties in a Dutch sample (45). Internal consistency was good (α = .79).…”
Section: Instrumentsmentioning
confidence: 99%
“…The disease-specific Lancashire Quality of Life Profile (LQoLP), intended for people with mental health problems, was used in seven studies. This instrument was later described as influencing the development of the FQL (Schel et al, 2017). The LQoLP was in turn based on, and a somewhat shorter version of, the disease-specific Lehman Quality of Life Interview (LQOLI), which was used in six studies.…”
Section: Table 2 (Continued)mentioning
confidence: 99%